Social Pedagogy in Spain: From academic and professional reconstruction to scientific and social uncertainty - Martí Xavier March Cerdà; Carmen Orte Socias; Lluís Ballester Brage (Sociedad Iberoamericana de Pedagogía Social, 2015)
Introduction and aims: A reflection on the reality of Social Pedagogy in Spain during the second decade of the 21st century from an analytical perspective, with the aim of finding out and recognising its weak points, its strong points, its challenges and its opportunities. The analysis centres on reviewing Social Pedagogy as a key discipline  in the reconstruction of Educational Sci- ences and a socio-educational response to the demands and needs of society and the Welfare State. Analysis of the current situation is completed with research into Social Education studies. The sphere of reference is made up of the group of universities offering social education courses in Spain. The variables structuring the data capture were: 1) the structure of the offer, 2) the fea- tures of the courses offered, and 3) course results. Methodology: The sample taken was structural in nature, selecting 11 universities holding the courses in three areas of Spain - the North, Central and Southern Spain and the Mediterranean region. Information was gathered using two comple- mentary methodologies, a questionnaire, falling within the context of the Ibero-American Social Education Society (SIPS), and a review of the web sites of the universities offering courses in so- cial education. Data processing and analysis: The analysis was carried out in two complementary stages. First of all, the closed questions were processed using SPSS and then the digital records of the open questions were processed using the NVIVO program. Results: The large majority of the courses on offer are classroom-based, with some distance learning courses being available. The average size of the courses was around 87 places. It should be pointed out that the double degree in Social Education and Social Work on offer is merely symbolic. There is multi-departmental in- volvement in teaching the Degree, although a larger role is played by the Pedagogy departments and all socio-educational fields are involved. Within the most important skills, diagnostics and proj- ect design and management stand out. The professors teaching the courses are highly qualified and, with respect to teaching methodologies and assessments, these have changed and broadened out since the course was first held. Discussion: Theoretical reflection and data analysis is used to discuss the chance for Social Education to overcome the impasse in which it currently finds itself, in spite of the development and growth in social education studies over the last twenty years. The need is discussed to include evidence-based  research as a basis for socio-educational action and as a necessity to continue to move forward in Social Education and the qualification of socio-educational professionals.